THE INFLUENCE OF PROFITABILITY AND LIQUIDITY ON SUKUK RATINGS OF COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Mohammad Sya’roni; Haqiqi Rafsanjani; Rifa’atul Maftuhah (RADJA PUBLIKA, 2025)
This study aims to analyze the effect of profitability and liquidity on sukuk ratings in companies listed on the Indonesia Stock Exchange for the period 2021–2024. Profitability is measured using Return on Assets (ROA) and liquidity is measured by Current Ratio (CR). The research method uses panel data regression analysis with the Random Effect Model (REM) approach, after going through the Chow, Hausman, and Lagrange Multiplier tests. The results of the study show that profitability does not have a significant effect on sukuk ratings, while liquidity has a significant effect. The coefficient of determination (Adjusted R²) of 8.15% indicates that profitability and liquidity together are able to explain the variation in sukuk ratings by 8.15%, the rest is explained by other variables outside the model. These findings provide insight for investors in considering the liquidity aspect as the main indicator in assessing the risk and potential returns from sukuk investments.